Epistaxis and Its Associated Factors Among Precollege Students in Southern Ethiopia - Ameya, Gemechu (J Blood Med, 2021)
BACKGROUND: Epistaxis is one of the most common otorhinolaryngological emergencies affecting the majority of the population in their lifetime, with some of them requiring serious medical attention. This study aimed to assess the prevalence and associated factors of epistaxis among pre-college students in Wolaita Sodo, Ethiopia. METHODS: An institution-based cross-sectional study was conducted. Data were collected using a pre-tested interviewer administered questionnaire. The study participants were selected by systematic random sampling technique. A logistic regression analysis was employed to assess the presence and strength of association factors with epistaxis. An adjusted odds ratio with 95% confidence interval was used to determine the presence and strength of the association at 0.05 level of significance. RESULTS: Of 387 participants, 57.1% of them were male, and the mean age of all participant was 18.05±1.401 SD years. The overall epistaxis prevalence was 108 (27.9%). Blood group O, which accounted for about 43.4% was more prevalent. Blood group O (AOR=3.96, 95% CI=1.5–10.4), participants who drink coffee daily (AOR=2.75, 95% CI=1.0–7.4), and participants who took a bath frequently with both hot and cold-water (AOR=4.55, 95% CI=1.1–18.6) were significantly associated with epistaxis. CONCLUSION: The type of blood group, interval of coffee drinking, and type of bathing were significantly associated with epistaxis. Working on the identified associated factor and increased awareness about epistaxis for the students with effective first aid training is mandatory.